Barangay Anti-Drug Abuse Council’s (BADAC) Drug Clearing Program: Basis for the Development of Community Rehabilitation Program for Drug Surrenderees - Rebusquillo, Saerel (JPAIR Multidisciplinary Research, 2020)
The social and medical problems of drug abuse are a matter of increasing global concern. The government, through its joint efforts with the concerned agencies, the authorities, and criminal justice professionals, sought to find solutions to address the problems on illegal drugs. Unfortunately, until now, it has not been solved. The war on drugs became an unending process of killings and repeated use of drugs. This study aimed to evaluate the extent of implementation of the Barangay Drug Clearing Program and the problems encountered in Albay province. To facilitate the study, the researcher used a descriptive method of research. The respondents of the study were the barangay officials, drug surrenderees, and police officers in the two selected municipalities and cities in the second district of Albay. The statistical techniques used in the study were weighted arithmetic mean, Kruskal Wallis H, and Mann Whitney u. The survey questionnaire was used to facilitate the collection of data from the respondents. Data revealed that the pre-operation phase, operation phase, and post-operation phase of BADAC’s drug clearing program are implemented. However, the topmost problem encountered is the lack of rehabilitation facilities. Thus, the program of BADAC is functional through the active participation of the barangay officials, but inevitable problems occur in its implementation.